The philosophy of art : an introduction - Gracyk, Theodore (Cambridge : Polity, 2012)
1 Meaning, Interpretation, and Picturing 1 Representations and pictures 2 Theories of picturing 3 Intentions and transparency in pictures and photographs 4 Indiscernible counterparts 5 Fine art 2 Art as Expression 1 Overview of expression theories 2 Tolstoy's account of expressive art 3 Collingwood's account of expressive art 4 The expressive persona 5 Expression as arousal 6 Revising the arousal theory 7 Expression as cognitive recognition 3 Meaning and Creativity 1 Plato on creativity 2 Kant on genius 3 Metaphorical exemplification 4 Hegel and Marx 5 Material bases of creativity 6 Feminism and creativity 4 Fakes, Originals, and Ontology 1 Multiples and singularities 2 Abstract objects 3 Problems and implications 4 Fakes and originals 5 Objections and alternatives 5 Authenticity and Cultural Origins 1 Two kinds of contextualism 2 Four kinds of appropriation 3 Moral concerns 4 Culture 5 Authenticity 6 Modernity and authenticity 6 Defining Art 1 Philosophical definition 2 Historical background 3 Functional definitions 4 Institutional definitions 5 Historical definitions 6 The cluster account 7 Aesthetics 1 Aesthetic judgments and properties 2 Supervenience 3 Two complications 4 Aesthetics and nature 5 Formalism and detachment 6 Making special 7 Pleasure and appreciation 8 Beyond the Fine Arts 1 Popular and mass art 2 Standard criticisms of popular art 3 Social consequences of popular culture 4 Gender and race 5 Everyday aesthetics 9 Artistic and aesthetic value 1 Three kinds of value 2 The uniqueness thesis 3 Value empiricism 4 Instrumental value 5 An alternative analysis 6 Appreciation 7 Cognitive value 10 Conclusion
boek